Improvements in Governance through Smart City Mission: Case Study Bhopal - Anshita Choudhary; Anshul Puriya; Afreen Ansari (Calibrating Urban Livability in the Global South, 2024)
The research study focuses on evaluating the Integrated Control and Command Center (ICCC) within the context of the Smart Cities Mission in Bhopal, Madhya Pradesh, with the primary objective of assessing its contribution to improving the quality of public service. Aligned with Sustainable Development Goal 11, the study aims to understand the influence of information and communication technology (ICT) in improving governance in Bhopal. The study places a significant emphasis on governance and citizen participation, recognizing that urban success extends beyond technological advancements. It seeks to unveil the depth of the ICCC’s contribution to these crucial aspects, providing policymakers with practical insights necessary for refining smart city initiatives to authentically address citizen needs. The research is indispensable for assessing the tangible benefits of the ICCC, aligning them with citizens’ expectations, and promoting a more responsive, citizen-centric approach to urban development. The data collection involves a mixed-method approach, combining surveying city residents and extracting information from existing databases, reports, and direct observations. The study focuses on two primary indicators: governance and citizen satisfaction. Initially, projects encompassed by the ICCC are identified and categorized into four pillars of good governance: Accountability, Participation, Rule of Law, and Transparency. Subsequently, citizen satisfaction is evaluated within these pillars, providing a structured analysis that delves into both the organizational governance aspects and the perception of citizens regarding the services facilitated by the ICCC. The paper not only adds depth to the understanding of the Smart Cities Mission but also serves as a valuable resource for policymakers and stakeholders involved in urban development initiatives.